A Pilot Screen of a Novel Peptide Hormone Library Identified Candidate GPR83 Ligands. (October 2020) - Sallee, Nathan A.; Lee, Ernestine; Leffert, Atossa; Ramirez, Silvia; Brace, Arthur D.; Halenbeck, Robert; Kavanaugh, W. Michael; Sullivan, Kathleen M. C.
The identification of novel peptide hormones by functional screening is challenging because posttranslational processing is frequently required to generate biologically active hormones from inactive precursors. We developed an approach for functional screening of novel potential hormones by expressing them in endocrine host cells competent for posttranslational processing. Candidate preprohormones were selected by bioinformatics analysis, and stable endocrine host cell lines were engineered to express the preprohormones. The production of mature hormones was demonstrated by including the preprohormones insulin and glucagon, which require the regulated secretory pathway for production of the active forms. As proof of concept, we screened a set of G-protein-coupled receptors (GPCRs) and identified protein FAM237A as a specific activator of GPR83, a GPCR implicated in central nervous system and regulatory T-cell function. We identified the active form of FAM237A as a C-terminally cleaved, amidated 9 kDa secreted protein. The related protein FAM237B, which is 64% homologous to FAM237A, demonstrated similar posttranslational modification and activation of GPR83, albeit with reduced potency. These results demonstrate that our approach is capable of identifying and characterizing novel hormones that require processing for activity.